2021
DOI: 10.1021/acssuschemeng.1c06066
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Viral Transmission of SARS-CoV-2 in Still Waterbodies Using a Lanthanide-Doped Carbon Nanoparticle-Based Sensor Array

Abstract: The latest epidemic of extremely infectious coronavirus disease 2019 (COVID-19) has created a significant public health concern. Despite substantial efforts to contain severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) within a specific location, shortcomings in the surveillance of predominantly asymptomatic infections constrain attempts to identify the epidemiological spread of the virus. Continuous surveillance of wastewater streams, including sewage, offers opportunities to track the spread of SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 113 publications
(182 reference statements)
0
20
0
Order By: Relevance
“…Though the nanosensor in the latter study was tested in a biofluid (saliva) matrix, its applicability for wastewater analysis needs to be explored further. A recent study developed a fluorescence sensing array using lanthanide-doped carbon nanoparticles (LnCNPs) for the detection of SARS-CoV-2 protein in wastewater samples [ 27 ]. The method was based on the selective binding of the LnCPs with the spike (S) glycoprotein of SARS-CoV-2.…”
Section: Non-pcr-based Methods: Applications and Recent Developmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the nanosensor in the latter study was tested in a biofluid (saliva) matrix, its applicability for wastewater analysis needs to be explored further. A recent study developed a fluorescence sensing array using lanthanide-doped carbon nanoparticles (LnCNPs) for the detection of SARS-CoV-2 protein in wastewater samples [ 27 ]. The method was based on the selective binding of the LnCPs with the spike (S) glycoprotein of SARS-CoV-2.…”
Section: Non-pcr-based Methods: Applications and Recent Developmentsmentioning
confidence: 99%
“…The relative fluorescence emission intensities of the LnCNPs (lanthanides: Gd(III), Pr(III), and Yb(III)) before and after the addition of viral sample were used to characterize the fluorescence signature of the LnCNPs against SARS-CoV-2. This recent study by Alafeef et al (2022) showed that the newly developed sensor coupled with a pattern recognition algorithm exhibited the following advantages: i) high sensitivity (LOD of 1.52 copies/μL), ii) selectivity in the detection of SARS-CoV-2 over other species (H1N1 virus, SARS-CoV-1, E.coli , B.subtilis, and S.mutans ) due to differences in fluorescence response patterns, and iii) elimination of the need for an antibody [ 27 ].…”
Section: Non-pcr-based Methods: Applications and Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test has a turn-around time of 15 min and operates in a label-free manner allowing use in-field and across areas with limited resources. 158 …”
Section: Diagnostic Tests Of Sars-cov-2 Based On Nanomaterials and 2d...mentioning
confidence: 99%
“…With the help of a machine-learning-based pattern recognition algorithm, SARS-CoV-2 viral transmission is still wastewater that can be detected and discriminated from other pathogens using the LnCNP-based sensor array. Reprinted with permission from ref ( 158 ). Copyright 2022 American Chemical Society.…”
Section: Diagnostic Tests Of Sars-cov-2 Based On Nanomaterials and 2d...mentioning
confidence: 99%